Templated self-assembly of wedge-shaped DNA arrays - Lubrich, D; Bath, J; Turberfield, A (Elsevier, 2008)
We demonstrate the use of a one-dimensional template to control the shape of a two-dimensional array self-assembled from a minimal set of DNA tiles. A periodic single-stranded template seeds tile assembly. A unique vertex tile at the 5′ end of the template controls the positioning of edge and body tiles to create a wedge-shaped array. The vertex angle of the array is approximately 12°; edge lengths are of the order of 1 μm. © 2008 Elsevier Ltd. All rights reserved.